NK Cells in the Human Lungs - Hervier, Baptiste; Russick, Jules; Cremer, Isabelle; Vieillard, Vincent (Frontiers in Immunology, 2019)
The lung offers one of the largest exchange surfaces of the individual with the elements of the environment. As a place of important interactions between self and non-self, the lung is richly endowed in various immune cells. As such, lung natural killer (NK) cells play major effector and immunoregulatory roles to ensure self-integrity. A better understanding of their abilities in health and diseases has been made possible over the past decade thanks to tremendous discoveries in humans and animals. By precisely distinguishing the different NK cell subsets and dissecting the ontogeny and differentiation of NK cells, both blood and tissue-resident NK populations now appear to be much more pleiotropic than previously thought. In light of these recent findings in healthy individuals, this review describes the different lung NK cell populations quantitatively, qualitatively, phenotypically, and functionally. Their identification, immunological diversity, and adaptive capacities are also addressed. For each of these elements, the impact of the mutual interactions of lung NK cells with environmental and microenvironmental factors are questioned in terms of functionality, competence, and adaptive capacities. As pulmonary diseases are major causes of morbidity and mortality worldwide, special attention is also given to the involvement of lung NK cells in various diseases, including infectious, inflammatory, autoimmune, and neoplastic lung diseases. In addition to providing a comprehensive overview of lung NK cell biology, this review also provides insight into the potential of NK cell immunotherapy and the development of targeted biologics.